Pengaruh Lingkungan Kerja dan Kepemimpinan terhadap Kinerja Karyawan Melalui Kepuasan Kerja pada PT. Mode Fashion Medan - Armansyah Ritonga; Syaiful Bahri (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2022)
The purpose of this study was to examine and analyze the effect of the work environment and leadership on employee performance through job satisfaction at PT. Fashion Fashion Medan directly or indirectly. The approach used in this study is a causal approach. The population in this study were all employees of PT. Medan Fashion. The sample in this study used a saturated sample of 107 employees of PT. Medan Fashion. Data collection techniques in this study used documentation, observation, and questionnaire techniques. The data analysis technique in this study used a quantitative approach using statistical analysis using the Auter Model Analysis test, Inner Model Analysis, and Hypothesis Testing. Data processing in this study using the PLS (Partial Least Square) software program. The results of this study indicate that the work environment, leadership and job satisfaction have a significant effect on employee performance and work environment and leadership has a significant effect on employee performance through employee job satisfaction at PT. Fashion Fashion Medan